Występowanie kornika drukarza Ips typographus (L.) (Coleoptera, Curculionidae, Scolytinae) po wiatrołomie z 2013 roku w Dolinie Kościeliskiej w Tatrzańskim Parku Narodowym - Grodzki, Wojciech; Gąsienica Fronek, Wojciech (Leśne Prace Badawcze, 2017)
At the end of 2013, Norway spruce stands in the area of the Tatra National Park were severely damaged by strong storms especially in the Kościeliska Valley region. In the following spring of 2014, a survey recording the occurrence of the spruce bark beetle Ips typographus (Coleoptera, Curculionidae, Scolytinae) was initiated in order to describe the dynamics of beetle reproduction in relation to protection measures executed in wind-damaged stands. Ten research plots with 20 trees each were established in a so-called active protection zone, where the broken and fallen trees had been processed and removed in 2014, and in a passive protection zone, where no actions were taken, and the dynamics of Norway spruce mortality due to bark beetle infestation including quantitative parameters (infestation density, sex ratio of beetle populations) were examined. The entomological analyses were performed on 25×25 cm large bark samples taken from four (active zone) or two (passive zone) tree sections. In the first year of the survey, no infested standing trees were recorded on the plots and the colonisation of fallen and broken trees was very weak. In the second year (2015), infestations appeared in larger numbers on the plots with passive compared to active protection but the infestation density was 0.89 mating chambers per 1 dm 2 regardless of the protection status. In the third year (2016), most of the remaining living spruces had been infested with a mean density of 0.82 m.ch. per 1 dm 2 . In 2015, the proportion of females in the beetle population was 65.8% being higher in the active (68.4%) than the passive (64.0%) protection zone, while in 2016 the proportion was 63.5% and in this case slightly higher in the passive protection zone (63.9% as compared to 63.2%). These results are in accordance with patterns observed in wind-damaged Norway spruce stands of other areas in Poland and Europe and demonstrate the usefulness of forest management procedures in mitigating I. typographus outbreaks.